Future directions for reducing inequity and maximising impact of child health strategies. (30th July 2018) - Dalglish, Sarah L; Vogel, Joanna J; Begkoyian, Geneviève; Huicho, Luis; Mason, Elizabeth; Root, Elisabeth Dowling; Schellenberg, Joanna; Estifanos, Abiy Seifu; Ved, Rajani; Wehrmeister, Fernando C; Labadie, Guilhem; Victora, Cesar G
Abstract : Current global child health strategies have reduced wealth based inequities in care seeking for childhood illness, but we need much greater emphasis on equity in strategy design and implementation, say Sarah L Dalglish and colleagues